PERLINDUNGAN HUKUM HAK PEMEGANG DESAIN INDUSTRI DIKAITKAN DENGAN NILAI KEBARUAN DI INDONESIA - Tengku Mega Rahmadini; Firdaus; Zulfikar Jayakusuma (JOURNAL EQUITABLE, 2023)
Weaknesses in the implementation of the Industrial Design Law are caused by a number of things, including the implementation of the rules mandated by the Industrial Design Law which have not been fully implemented by the government. Similarity is something that may occur even in industrial designs, designs must have a novelty principle. There is no clear measure of how much the percentage of similarity between the two types of products can be said to violate other people's industrial design rights. research or problem approach that will be used in this study is normative juridical, namely research conducted by examining secondary legal materials or research based on standard rules that have been recorded is also called library research.